Pensions at work : socially responsible investment of union-based pension funds - Carmichael, Isla; Quarter, Jack; Ryan, Sherida, 1949- (University of Toronto Press, 2008)
This collection moves the discussion to pension funds in which union representatives are also trustees, a relatively new approach that will be of great interest to institutional investors, the labour movement, and instructors in labour studies programs.